2016
DOI: 10.1136/rmdopen-2015-000197
|View full text |Cite
|
Sign up to set email alerts
|

Association of a multibiomarker disease activity score at multiple time-points with radiographic progression in rheumatoid arthritis: results from the SWEFOT trial

Abstract: ObjectivesIn rheumatoid arthritis (RA), predictive biomarkers for subsequent radiographic progression (RP) could improve therapeutic choices for individual patients. We previously showed that the multibiomarker disease activity (MBDA) score in patients with newly diagnosed RA identified patients at risk for RP. We evaluated the MBDA score at multiple time-points as a predictor of RP during 2 years of follow-up.MethodsA subset of patients with RA (N=220) from the Swedish Farmacotherapy (SWEFOT) trial were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…79 The correlation of the MBDA score with radiographic progression was weak (OR per unit of increase: close to 1.0 (1.0 to 1.1)). The association of higher (>44) MBDA scores and radiographic progression was better (OR vs low score 3.9 (1.0 to 14.3)), but, while the NPV for this cut-off was high (97%), the PPV did not exceed 20%; and thus MBDA scores appear to be of minor value for clinical practice.…”
Section: Resultsmentioning
confidence: 92%
“…79 The correlation of the MBDA score with radiographic progression was weak (OR per unit of increase: close to 1.0 (1.0 to 1.1)). The association of higher (>44) MBDA scores and radiographic progression was better (OR vs low score 3.9 (1.0 to 14.3)), but, while the NPV for this cut-off was high (97%), the PPV did not exceed 20%; and thus MBDA scores appear to be of minor value for clinical practice.…”
Section: Resultsmentioning
confidence: 92%
“…We previously showed in the SWEFOT trial that MTX‐IR patients receiving anti‐TNF therapy had a significantly lower proportion of radiographic progression at year 2 compared with those receiving triple therapy 18. However, in a later study of the same patients, it was shown that patients with low MBDA scores at the time of randomization did not progress radiographically during 2 years from baseline, regardless of the choice of therapy 28. Neither differed in the proportion of patients with 2‐year radiographic progression among those with moderate MBDA scores between the anti‐TNF and triple therapy groups (24% and 25%, respectively).…”
Section: Discussionmentioning
confidence: 95%
“…As for the prediction of response, the abilities of the MBDA test have yet to be investigated. However, it has been shown that the baseline MBDA score is a significant prognostic factor for radiographic progression, according to one study (26), but is not able to predict radiographic progression over time better than DAS28, according to another study (23). In addition, one study found hardly any correlation between the MBDA score and several disease activity measurements in RA patients treated with biologicals (27).…”
Section: Studymentioning
confidence: 98%